Chemical and physical properties of meat from Dezhou black donkey - Li, Mengmeng; Zhang, Demin; Chai, Wenqiong; Zhu, Mingxia; Wang, Yonghui; Liu, Yongxiang; Wei, Qingxin; Fan, Dongmei; Lv, Mengqing; Jiang, Xiaojing; Wang, Changfa (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2022)
Donkey meat is extremely popular in China owing to its high nutritional value and unique flavour. However, the physical and chemical properties of meat from the Dezhou black donkey have seldom been reported. This study aimed to compare differences in the physical characteristics, intramuscular fat (IMF) content, fatty acid profile, and antioxidant capacity of meat from Dezhou black donkey. The results showed that the L* and ΔE values of longissimus dorsi (LD) were significantly lower than those of gluteus maximus (GM) and biceps femoris (BF), while the b* value of LD was significantly higher than that of GM (p < 0.05). The shear force, hardness, adhesiveness, and elasticity values of LD and BF were significantly lower than those of GM (p < 0.05). The IMF content in LD was significantly higher than those in GM and BF (p < 0.05). The contents of fatty acids 15:0, 14:1, 18:2n-6, 20:4n-6, and polyunsaturated fatty acids in LD were significantly lower than those in GM and BF, while the 18:0, 18:1n-9, and monounsaturated fatty acid contents showed the opposite trend (p < 0.05). The superoxide dismutase activity of LD was significantly higher than those of GM and BF (p < 0.05), while the malonaldehyde content showed the opposite trend (p < 0.05). Overall, LD is an ideal edible part of Dezhou black donkey, owing to its higher IMF, tenderness, 18:1n-9, and antioxidant capacity levels, and lower 18:2n-6 and ΔE levels. This study provides novel insight into the development of donkey meat products.